Mapping gender stereotypes: a network analysis approach - Sánchez-Rodríguez, Ángel; Moreno-Bella, Eva; García-Sánchez, Efraín (Frontiers in Psychology, 2023)
Stereotypes have been traditionally considered as “mental pictures” of a specific social group. The current research aims to draw the structure of gender stereotypes and metastereotypes schemes as complex systems of stereotypical features. Therefore, we analyse gender stereotypes as networks of interconnected characteristics. Through an online survey (N = 750), participants listed the common female and male features to build the structure of the gender stereotypes. Furthermore, participants listed the common features about how members of one gender think of how they are viewed by the people of the other gender to build the structure of gender metastereotypes. Our results suggest that female stereotypes are characterized by a single community of features consistently associated such as intelligent, strong and hardworkers. Female metastereotype, however, combines the previous community with another characterised by weak and sensitive. On the other hand, the male stereotype projected by women is characterized by a community of features associated such as intelligent, strong and hardworker; but male in-group stereotypes and metastereotypes projected by men are a combination of this community with another one characterised by features associated such as strong, chauvinist and aggressive. Moreover, the network approach provided some insight into the meaning of some features when they are considered linked to different features (e.g., strong-intelligent vs strong-aggressive). The theoretical and practical implications of examining gender stereotypes from a network perspective are discussed.